THE FUTURE OF INDONESIA AND GLOBAL AGRICULTURE: RICE CONSUMPTION AND AGRICULTURAL MODERNIZATION - Ade Marsinta Arsani (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2020)
In the industry revolution 4.0 era, the agriculture sector still has an important position in human life because, without this sector, human capital development cannot be well developed. Globally, the share of agriculture, forestry, and fishing sector has declined significantly in the last two decades. However, the demand on agriculture product, especially rice, incline every year. Rice supply and demand projection with appropriate methods are very important because their result affect how agricultural policies are applied. The aim of this study is to examine the likely evolution of rice consumption in Indonesia and forecast the Indonesia rice consumption per capita based on global data. The results indicate the income elasticity of demand for rice in the Indonesia has become negative. The forecast of model show that Indonesia’s rice demand will keep incline, at least in the next five years. Due to those result, in order to maintain farmers’ wealth, modernization in agriculture is needed. Government has encouraged some programs such as Simluhtan, Katam, Si Mantap, Smart Farming, Smart Green House, Autonomous Tractor, dan Smart Irrigation to accelerate the agricultural transformation. Unfortunately, human resource quality becomes a problem. Indonesia need massive effort so that modernization in agriculture works well.